2019
DOI: 10.3390/educsci9040297
|View full text |Cite
|
Sign up to set email alerts
|

Nonscientific University Students Training in General Science Using an Active-Learning Merged Pedagogy: Gamification in a Flipped Classroom

Abstract: Innovative teaching strategies are designing a new and promising landscape in education. They fill lessons with creativity and imagination for either the students or teachers. This article addresses an attempt to make the approach to science easier in a nonscientific environment: primary education at university level. Gamification methodologies were combined with a flipped classroom in order to free up in-class time and engage the students with the taught courses. A qualitative study was merged with quantitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 30 publications
1
48
0
9
Order By: Relevance
“…Emotions were also analysed because of their intimate relationship with motivation, especially internal motivation ( Zamora-Polo et al., 2019a ). For the analysis of emotions (question 5), they were classified into relevant categories and their graphical representation was used for comparing both groups (Education and Engineering).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Emotions were also analysed because of their intimate relationship with motivation, especially internal motivation ( Zamora-Polo et al., 2019a ). For the analysis of emotions (question 5), they were classified into relevant categories and their graphical representation was used for comparing both groups (Education and Engineering).…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with emotional performance of students shown previously. Previous studies have shown that science and technology-related courses often produce negative emotions ( Novak and Wisdom, 2018 ; Sánchez-Martín et al., 2017c ) and that student-centered learning activities lead to positive emotional performance ( Jeong et al., 2018 ; Jeong et al., 2019 ; Novak and Wisdom, 2018 ; Sánchez-Martin et al., 2018 ; Suwal and Singh, 2018 ; Zamora-Polo et al., 2019a ), increasing positive emotions in students. Student responses seem to indicate that these activities are attractive, and that they consider them useful both for the development of specific skills and for the development of transversal skills.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, in the introduction, the authors reflect on how teaching sciences in higher education to a non-scientific audience [10] according to the scientific method. In detail, to facilitate the future reply, a step-by-step description of the methodology is given.…”
Section: Introductionmentioning
confidence: 99%